PARTISIPASI POLITIK PENGUSAHA PADA PEMILIHAN UMUM LEGISLATIF DI KABUPATEN KUANTAN SINGINGI TAHUN 2014 - Herianto, Meki; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Occupy the position of the Trend businessman strategic positions in political party not only at the national level, but it has already been spreads to the regions. One of the areas are Kuantan Singingi. According to Bpk Dedi Rukmana members of the General Election Commission Kuansing said nearly 100% members of the House of Representatives Regional House Kuansing chosen are) politicians who had his background as a businessman. Problem political participation Legislative Election entrepreneurs in the Regency of Kuantan Singingi in 2014?Research method that is applied in this study is descriptive qualitative analysis method that is trying to present based on the phenomena that are and to all the facts related to problems that discussed the political participation Legislative Election Entrepreneurs In the Regency of Kuantan Singingi in 2014.Participation of the entrepreneur results of the study showed legislative election in the Regency of Kuantan Singingi in 2014 to form sponsor the campaign, to form a team success, to legislative candidate, participate in kapanye, discussion politics, to vote and have a high motivation that varies in each businessman.Key words : Participation, Politics, an entrepreneur